Participatory Ethnomedicinal Cancer Research with Fante-Akan Herbalists in Rural Ghana - Summer Ragosta; Ivelyn Harris; Ntim Gyakari; Emmanuel Otoo; Alex Asase (Ethnobiology Letters, 2015)
An ethnomedicinal study was initiated with herbalists in coastal Central Region Ghana to explore how cancer is defined, diagnosed, and treated within a traditional Fante-Akan context. The participatory, service-oriented investigation included international collaboration with herbalists and traditional plant experts. On-site meetings informed community leaders and members of project intent and methods, guided protocol, and gauged critical support. To provide immediate educational and economic opportunities, hands-on activities with villagers transferred academic and applied skills. Ethnographic interviews and voucher specimen collections were conducted with seven herbalists. Plant samples were dried and housed locally in a community herbarium cabinet constructed in Kormantse. Ten cancer ethnopharmacopoeia plants were identified, most of which are species considered native to tropical Africa. Fante Akan herbalists listed various types of cancers they treat with herbal remedies, along with ethnomedicinal descriptions of disease etiology, diagnoses, and treatments. The most common cancer type mentioned was “breast cancer.” Topical application was the most often cited method of administering remedies. Researchers established key contacts in the Kormantse, Salt Pond, and Elmina communities, and identified local and international research collaborators for a proposed interdisciplinary project focused on longitudinal case studies with herbalists, patients, and medical physicians.